2014
DOI: 10.1007/s11940-014-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mitochondrial Disorders

Abstract: Opinion statement While numerous treatments for mitochondrial disorders have been suggested, relatively few have undergone controlled clinical trials. Treatment of these disorders is challenging, as only symptomatic therapy is available. In this review we will focus on newer drugs and treatment trials in mitochondrial diseases, with a special focus on medications to avoid in treating epilepsy and ICU patient with mitochondrial disease, which has not been included in such a review. Readers are also referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 98 publications
2
80
0
1
Order By: Relevance
“…Antioxidant quinones (e.g. coenzyme Q10 (CoQ10), idebenone) have been used clinically to prevent the disease progression (Avula et al 2014;Enns 2014), but the effectiveness of such quinones has not been well established (Pfeffer et al 2012). Therefore, an alternative effective therapeutic approach is still urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant quinones (e.g. coenzyme Q10 (CoQ10), idebenone) have been used clinically to prevent the disease progression (Avula et al 2014;Enns 2014), but the effectiveness of such quinones has not been well established (Pfeffer et al 2012). Therefore, an alternative effective therapeutic approach is still urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…While discussion of each agent's detailed mechanism of action in PMD/SMD is beyond the scope of this review, we have highlighted the most commonly used ubiquinone (CoQ10) and provided examples of some combination therapies. Even though Pfeffer et al [2012] concluded that there is no clear evidence supporting any interventions in mitochondrial disorders, more promising trials have been conducted recently and are currently in process [Kerr, 2013;Avula et al, 2014;Enns, 2014;Tischner and Wenz, 2015].…”
Section: Treatmentmentioning
confidence: 99%
“…Certain drugs have the potential to be detrimental in the context of a mitochondrial disorder and should be avoided or used with caution 40. These include sodium valproate (risk of hepatotoxicity, and contraindicated in patients with POLG mutations) and anaesthetic agents such as propofol 41…”
Section: Management Of Mitochondrial Disordersmentioning
confidence: 99%